Psychopharmacology of 5-HT(1A) receptors. - Cowen, P (2000)
Serotonin(1A) (5-HT(1A)) receptors are located on both 5-HT cell bodies where they act as inhibitory autoreceptors and at postsynaptic sites where they mediate the effects of 5-HT released from nerve terminals. The sensitivity of 5-HT(1A) receptors in humans can be measured using the technique of pharmacological challenge. For example, acute administration of a selective 5-HT(1A) receptor agonist, such as ipsapirone, decreases body temperature and increases plasma cortisol through activation of pre- and postsynaptic 5-HT(1A) receptors, respectively. Use of this technique has demonstrated that unmedicated patients with major depression have decreased sensitivity of both pre- and postsynaptic 5-HT(1A) receptors. Treatment with selective serotonin reuptake inhibitors further down-regulates 5-HT(1A) receptor activity. Due to the hypotheses linking decreased sensitivity of 5-HT(1A) autoreceptors with the onset of antidepressant activity, there is current interest in the therapeutic efficacy of combined treatment with selective serotonin reuptake inhibitors and 5-HT(1A) receptor antagonists.